Creativity Style and Achievements: An Investigation on the Role of Emotional Competence, Individual Differences, and Psychometric Intelligence - Nori, Raffaella; Signore, Stefania; Bonifacci, Paola (Frontiers in Psychology, 2018)
Psychometric and emotional intelligence are considered as two separate theoretical constructs, although each one has been found to correlate to a certain degree with measures of creativity. The aim of the present study was to analyze whether individual differences such as age and gender, together with psychometric intelligence and emotional competence predicted creativity. We selected a sample of 376 participants aged 12-88 (mean age = 30.28 years, S.D. = 19.09; 224 females) to evaluate relationships between these constructs across lifespan. Participants were administered the Kaufman Brief Intelligence Test-2, the Short Profile of Emotional Competence (EC), the Creativity Style Questionnaire Revised (CSQ-R) and the Creativity Achievement Questionnaire (CAQ). A series of hierarchical regressions revealed that educational level (Beta = .12, t = 2.33, p <.05) and Interpersonal EC (Beta = .17, t = 3.10, p < .01) predicted beliefs and potential creativity style, whereas age (Beta = -.20, t = -3.99, p <.001), gender (Beta = -.12, t = -2.40, p <.05), IQ composite (Beta = .10, t = 2.11, p < .05) and Interpersonal EC (Beta =.12, t = 2.324, p < .05) predicted creativity achievements (arts, sports and other domains). Discussion is focused on possible theoretical implications.